Topological phase diagram of a three-terminal Josephson junction: From the conventional to the Majorana regime - Peralta Gavensky, Lucila (2019)
We study the evolution of averaged transconductances in three-terminal Josephson junctions when the superconducting leads are led throughout a topological phase transition from an s-wave to a p-wave (Majorana) phase by an in-plane magnetic field Bx. We provide a complete description of this transition as a function of Bx and a magnetic flux φ threading the junction. For that we use a spinful model within a formalism that allows us to treat on an equal footing the contribution to the transconductance from both the Andreev subgap levels and the continuum spectrum. We unveil a fractionalization in the quantization of the transconductance due to the presence of Majorana quasiparticles, reflecting the effective pumping of half a Cooper pair charge in the p-wave regime.